Alanine tails signal proteolysis in bacterial ribosome-associated quality control - Lytvynenko, Iryna; Paternoga, Helge; Thrun, Anna; Nagler, Katja; Anders, Simon; Bischofs-Pfeifer, Ilka; Joazeiro, Claudio A. P. (Cell, 2019)
In ribosome-associated quality control (RQC), Rqc2/NEMF closely supports the E3 ligase Ltn1/listerin in promoting ubiquitylation and degradation of aberrant nascent-chains obstructing large (60S) ribosomal subunits-products of ribosome stalling during translation. However, while Ltn1 is eukaryote-specific, Rqc2 homologs are also found in bacteria and archaea; whether prokaryotic Rqc2 has an RQC-related function has remained unknown. Here, we show that, as in eukaryotes, a bacterial Rqc2 homolog (RqcH) recognizes obstructed 50S subunits and promotes nascent-chain proteolysis. Unexpectedly, RqcH marks nascent-chains for degradation in a direct manner, by appending C-terminal poly-alanine tails that act as degrons recognized by the ClpXP protease. Furthermore, RqcH acts redundantly with tmRNA/ssrA and protects cells against translational and environmental stresses. Our results uncover a proteolytic-tagging mechanism with implications toward the function of related modifications in eukaryotes and suggest that RQC was already active in the last universal common ancestor (LUCA) to help cope with incomplete translation.